Pengaruh Economic Pressure dan Social Pressure terhadap Kualitas Pengungkapan Emisi Karbon: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Astuti, Helma Sri; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2025)
The purpose of this research is to analyze the impact of economic pressure and social pressure on the quality of emission of carbon disclosure in mining companies in Indonesia during the period 2020-2022. The emission of carbon disclosure has become increasingly important due to rising global attention to environmental issues and pressure from various stakeholders to improve transparency regarding corporate carbon emissions. The emission of carbon quality disclosure is the dependent variable in this research, while social and economic pressure are the independent variables. Using secondary data through the sustainability and annual data of mining companies listed on the Indonesia Stock Exchange, this study uses a quantitative approach that involves multiple linear regression analysis. The findings indicate that while economic pressure has no discernible effect on the of emission of carbon quality disclosure, social pressure significantly improves it. These findings highlight the critical role of social pressure in encouraging companies to disclose carbon emission-related information. However, the findings also suggest that economic factors do not influence the quality of such disclosures. Therefore, this study recommends adding other variables in future research to gain a more understanding in comprehensive for factors influencing carbon emission disclosure.